Relationships of stroke rate, distance per stroke, and velocity in competitive swimming - Craig, A. B. , Jr.; Pendergast, D. R. (Medicine & Science in Sports & Exercise, 1979)
The stroking rate and distance per stroke were evaluated against different swimming speeds in all four strokes. It was found that: - as speed increased so did stroke rate but distance per stroke decreased; - there was an optimal rate of stroking associated with the fastest swimming speed; - there was an optimal distance per stroke associated with the fastest swimming speed; - in crawl stroke, the fastest swimmers had the greatest distance per stroke at slow swimming speeds; - findings for backstroke were similar to crawl stroke; - increases in butterfly speed were almost entirely related to increases in stroke rate; and - breaststroke also displayed an increase in stroke rate but also showed the greatest reduction in distance per stroke at maximum speed. Implications: The stroking rate used by swimmers during training will generally be slower than that associated with the rate appropriate for the fastest race speed. Coaches should learn to distinguish between the optimal desirable rate and less desirable rates of stroking for more accurate race analysis. As the rate increases, the distance per stroke decreases, but only up to a point. When the two are optimized for a swimmer, the fastest performance will be possible. Measuring stroke rate and the number of strokes per lap (a measure of distance per stroke) can be used to tell when an athlete is or is not performing optimally.